AI-BASED SIMULATION TRAINING, CLINICAL SCENARIOS, AND DIGITAL ASSESSMENT IN OSCE PROCESSES. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The integration of artificial intelligence (AI) into simulation-based medical training has transformed traditional approaches to clinical skill development and assessment. This article examines AI-powered simulation platforms that replicate realistic clinical scenarios and enable digital evaluation within Objective Structured Clinical Examinations (OSCE). By employing machine learning algorithms for real-time performance scoring, adaptive scenario generation, natural language processing for patient interaction, and automated feedback mechanisms, AI delivers objective, bias-reduced, and personalized assessment of trainees’ diagnostic, procedural, and communication competencies.